A COMPARATIVE STUDY OF ISLAMIC AND SOUTH AFRICAN LAW ON LIVING AND CADAVERIC ORGAN DONATIONS: CONSENSUS AND DIVERGENCE - SS Nadvi; M Osman-Hyder (Obiter, 2021)
Religion plays a pivotal role in people’s attitude to organ donation. Generally, practising Muslims (adherents of the Islamic faith) are unlikely to consent to organ donation because they believe it is not in keeping with the tenets of Islamic law (Sharī`ah). Although there is a wealth of information on organ donation with reference to both South African and Islamic law, there has not been a study comparing the two sets of laws. The purpose of this article is to develop the literature on living and cadaveric organ donation by drawing a comparison between Islamic law and South African law on this issue. Apart from a few minor differences inherent in each set of laws, there is a startling consensus in South African law and Sunnī (mainstream) Islamic law on the issue of organ donation. This research is also significant in that it provides legal and medical professionals, academics and practitioners with an informed position from which to advise clients and/or patients. This may in turn raise awareness among clients and/or patients, which could result in a desirable increase in organ donation rates among Muslims in South Africa. This article makes a number of recommendations in this regard.